2020
DOI: 10.3389/fevo.2020.558833
|View full text |Cite
|
Sign up to set email alerts
|

Environment and Space Rule, but Time Also Matters for the Organization of Tropical Pond Metacommunities

Abstract: Gálvez et al. Time Shaping Tropical Temporary Ponds interpreted as related to generation time. Finally, when analyzing each sampling period separately, we found differences in the relative role of environment and space at different sampling periods, showing that snapshot surveys may not be representative of highly dynamic metacommunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 83 publications
4
24
2
Order By: Relevance
“…Therefore, our results differed from the original postulations on the expected seasonal patterns of assembly processes in temporary freshwater habitats, as the relative importance of environmental variables was higher in the early wet phase and the relative importance of spatial variables increased in the late drying periods. Our result also contrasts with studies that found the temporal variation of invertebrate composition to be solely associated with environmental conditions (Boix et al, 2016;Castillo-Escrivà et al, 2017;Vanschoenwinkel et al, 2010), and, at least for the study area as a whole, shows the opposite trend compared to the study of Gálvez et al (2020) in which the relative importance of the pure spatial fraction decreased over time.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, our results differed from the original postulations on the expected seasonal patterns of assembly processes in temporary freshwater habitats, as the relative importance of environmental variables was higher in the early wet phase and the relative importance of spatial variables increased in the late drying periods. Our result also contrasts with studies that found the temporal variation of invertebrate composition to be solely associated with environmental conditions (Boix et al, 2016;Castillo-Escrivà et al, 2017;Vanschoenwinkel et al, 2010), and, at least for the study area as a whole, shows the opposite trend compared to the study of Gálvez et al (2020) in which the relative importance of the pure spatial fraction decreased over time.…”
Section: Resultscontrasting
confidence: 99%
“…This is because species with reduced dispersal ability (e.g., passive dispersers) are expected to have their distributions strongly constrained by dispersal limitation (especially at broader spatial scales), whereas species with higher dispersal ability (e.g., active dispersers) could homogenize the composition of local communities due to increased movements across the landscape (de Bie et al, 2012;Heino, Melo, Siqueira, et al, 2015;Leibold & Chase, 2018). Particularly in metacommunity studies conducted in freshwater ecosystems, passive-dispersing taxa (e.g., crustaceans and molluscs) exhibit more dispersal limitation to their distributions than active-dispersing taxa (e.g., insects) (Bacca et al, 2020;de Bie et al, 2012;Declerck et al, 2011;Heino, 2013), although this is not a universal rule (Gálvez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metacommunity studies focusing on distinct organisms within the same landscape and localities revealed strong differences among taxa regarding dispersal limitation versus environmental selection (Beisner et al 2006;Padial et al 2014;Gálvez et al 2020). Variation in dispersal mode and body size have been considered important features associated with dispersal capacity and, consequently, modulating the strength of environmental filtering and dispersal limitation (De Bie et al 2012).…”
Section: Introductionmentioning
confidence: 99%